Technological Tools in Higher Education: A Qualitative Analysis from the Perspective of Students with Disabilities - José Fernández-Cerero; Julio Cabero-Almenara; Marta Montenegro-Rueda (MDPI AG, 2024)
The integration of information and communication technologies (ICT) in education has emerged as a transformative element, contributing significantly to the establishment of more inclusive educational environments. In this context, understanding the impact of technological tools becomes crucial to identifying the opportunities and limitations that students encounter when incorporating these resources in university classrooms. The main objective of this research is to analyse the impact of ICT use in higher education, with a specific focus on the perceptions of students with disabilities. Information was collected through interviews with university students with disabilities. The results reveal both advantages and difficulties and underline the importance of designing and implementing technologies in an inclusive way. Key issues relating to accessibility and participation are addressed, providing valuable insights for improving inclusive higher education in the digital age.